2014
DOI: 10.1002/anie.201406836
|View full text |Cite
|
Sign up to set email alerts
|

Intercrossed Carbon Nanorings with Pure Surface States as Low‐Cost and Environment‐Friendly Phosphors for White‐Light‐Emitting Diodes

Abstract: As an important energy-saving technique, white-light-emitting diodes (W-LEDs) have been seeking for low-cost and environment-friendly substitutes for rare-earth-based expensive phosphors or Pd(2+)/Cd(2+)-based toxic quantum dots (QDs). In this work, precursors and chemical processes were elaborately designed to synthesize intercrossed carbon nanorings (IC-CNRs) with relatively pure hydroxy surface states for the first time, which enable them to overcome the aggregation-induced quenching (AIQ) effect, and to em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
115
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 245 publications
(125 citation statements)
references
References 36 publications
7
115
0
3
Order By: Relevance
“…[50] Figure S1 (Supporting Information) shows S-AIMs with irregular shapes and randomly distributed particle size at 0.5-50 µm, which are www.advmattechnol.de further confirmed by the scanning electron microscopy (SEM) images in Figure 3b. [23,27,51] S-AIMs can effectively solve this issue since the PQD mean size of 22 nm ( Figure S4, Supporting Information) is comparable to the S-AIM mean pore size of 20 nm ( Figure S5, Supporting Information). These random pore structures and the rough surface lead to a combined effect, preventing the ambient moisture from penetrating into the S-AIMs, and as will be discussed in the following, serve for protecting the PQDs.…”
Section: Resultsmentioning
confidence: 99%
“…[50] Figure S1 (Supporting Information) shows S-AIMs with irregular shapes and randomly distributed particle size at 0.5-50 µm, which are www.advmattechnol.de further confirmed by the scanning electron microscopy (SEM) images in Figure 3b. [23,27,51] S-AIMs can effectively solve this issue since the PQD mean size of 22 nm ( Figure S4, Supporting Information) is comparable to the S-AIM mean pore size of 20 nm ( Figure S5, Supporting Information). These random pore structures and the rough surface lead to a combined effect, preventing the ambient moisture from penetrating into the S-AIMs, and as will be discussed in the following, serve for protecting the PQDs.…”
Section: Resultsmentioning
confidence: 99%
“…The resulting combination of yellow light with the residual blue light produces white light as perceived by the human eye12345. These phosphors should efficiently down-convert the blue photon and should maintain good optical performance even at an elevated ambient temperature.…”
mentioning
confidence: 99%
“…Previous studies have reported on several types of carbon nanorings and are shown in Table 1 . The N‐CNRs synthesized by our method have advantages including a rapid reaction time, flexible reaction atmospheric conditions, and low reaction temperature for production when compared to previous studies . The comparison details are summarized in Table .…”
Section: Comparison Between Three Types Of Previously Studied Carbon mentioning
confidence: 99%